2013
DOI: 10.1164/rccm.201304-0716up
|View full text |Cite
|
Sign up to set email alerts
|

Update in Lung Cancer and Mesothelioma 2012

Abstract: Lung cancer remains the number one cause of cancer-related death in the United States among both men and women. It is estimated that in 2013, there will be more than 200,000 new diagnoses of lung cancer and nearly 160,000 deaths (1). Despite the discovery and application of targeted therapies, the overall survival (OS) remains poor, with an overall 5-year survival approximating 16%. In addition, there are a growing number of cases among former smokers and never smokers. However, based on research advances in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 126 publications
1
18
0
Order By: Relevance
“…Pulmonologists see patients at risk for developing lung cancer that may benefit from an effective screening program. The increased use of detailed CT imaging has led to the increased identification of lung nodules, and this prevalence will increase in the era of CT-based screening (9,10). Advances in the evaluation of lung nodules include the use of guided bronchoscopy procedures performed by the pulmonologist, such as electromagnetic navigation, endobronchial ultrasound, and virtual bronchoscopic navigation.…”
Section: Epidemiology Risk Factors and Screeningmentioning
confidence: 99%
“…Pulmonologists see patients at risk for developing lung cancer that may benefit from an effective screening program. The increased use of detailed CT imaging has led to the increased identification of lung nodules, and this prevalence will increase in the era of CT-based screening (9,10). Advances in the evaluation of lung nodules include the use of guided bronchoscopy procedures performed by the pulmonologist, such as electromagnetic navigation, endobronchial ultrasound, and virtual bronchoscopic navigation.…”
Section: Epidemiology Risk Factors and Screeningmentioning
confidence: 99%
“…Despite the discovery and application of advanced therapies, the overall 5-year survival rate with lung cancer is only 16% [1,2] . It is often diagnosed as advanced disease because of its rapid growth and early tendency to spread to distant organs [3] .…”
Section: Introductionmentioning
confidence: 99%
“…This study, including 1 562 patients undergoing thoracic surgery, shows that over last 25 years, adenocarcinoma became the most frequent lung cancer histological type, that the proportion of women and non-smokers diagnosed with lung cancer increased, and that more early stages (stage I) were treated by surgery [14][15][16][17][18][19]. We observed that, as a whole, patients undergoing surgery for lung cancer diagnosed since 2003, when PET, and AT began to be adopted in daily practice, had a better 1 year and 2 years survival than those diagnosed before.…”
Section: Discussionmentioning
confidence: 91%